Letter - Winstanley, E.
029-0047-001 Telegraphic address: "Wholesale Manchester" Telephone: Blackfriars 1212 Extension Please address your reply: Co-operative Wholesale Society Limited. Central Offices, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C., 6th and 7th editions; Western Union 5 letter; Bentley Complete Phrase; Bentley Second Phrase, and Private. Our reference EXPORT ST/HP. 345 Your reference 11th January, 1938. The Trades Union Congress General Council, Transport House, Smith Square, London. Dear Sirs, Further to our letter of the 7th instant, we now have pleasure in attaching hereto invoices in respect of goods shipped by s.s. HARTBRIDGE from Newcastle to Oran for Barcelona, which you will doubtless find in order. We have still not received the charges for loading and demurrage from the loading brokers at Newcastle, but these will follow as early as possible. Meanwhile, we remain, Yours faithfully, E. Winstanley Export Department. 292/946/29/47